FAKTOR RISIKO TERJADINYA KEJADIAN IKUTAN PASCA IMUNISASI (KIPI) PADA PENERIMA VAKSIN COVID-19 DOSIS PERTAMA DI KECAMATAN CIMANGGIS KOTA DEPOK TAHUN 2021 - Septi Meline Dewi, (2022)
Serious adverse events following immunization (AEFI) after COVID-19 vaccination can cause concern in the community and affect public interest in participating in vaccination, so that COVID-19 control can be obstructed. The purpose of this study was to determine the risk factors for the occurrence of AEFI after receiving the first dose of the COVID-19 vaccine in Cimanggis District, Depok City. The study design used was cross-sectional. The number of samples was 304 respondents who were taken by purposive sampling technique. Respondents filled out an online questionnaire with google forms. Multivariate analysis showed that there were three variables related to AEFI. The most related variable with AEFI was the type of vaccine (POR:9,687, 95% CI:5,368-17,478). In addition, there was an association between gender (POR: 0.497, 95% CI: 0.286-0.864) and a history of having been infected with COVID-19 before receiving the vaccine (POR: 0.497, 95% CI: 1.175-4.088) on the occurrence of AEFI. It is hoped that the government can socialize AEFI to the public before and after the community receives the vaccine. The community is also expected to improve their health in order to have a good immune system.